Infection with Ureaplasma urealyticum: is there a specific clinical and radiological course in the preterm infant?. Issue 2 (1st March 2004) - Theilen, U; Lyon, A J; Fitzgerald, T; Hendry, G M A; Keeling, J W
Abstract : Background: Despite having mild early respiratory disease, many preterm babies develop chronic lung disease (CLD). Intrauterine infection with Ureaplasma urealyticum has been associated with preterm labour and CLD. Objective: To test the hypothesis that infection with U urealyticum results in a specific clinical and radiological picture in the first 10 days of life. Methods: Retrospective study of 60 ventilated babies < 30 weeks gestation, who had tracheal secretions tested for U urealyticum . Placental histology was reviewed by a paediatric pathologist for signs of chorioamnionitis. Chest radiographs were independently reviewed by two paediatric radiologists according to previously agreed criteria. All reviewers were blinded to the infection status of the babies. Results: Twenty five babies were U urealyticum positive. These were more likely to experience chorioamnionitis (p = 0.004), premature rupture of membranes (p = 0.01), and spontaneous vaginal delivery (p = 0.09). U urealyticum positive babies had fewer signs of respiratory distress syndrome on early chest radiographs (p = 0.038), and they could be weaned from their ventilation settings (fraction of inspired oxygen (Fio 2 ) and mean airway pressure) more quickly in the first few days. Subsequently U urealyticum positive babies deteriorated clinically and radiologically. More often they required ventilation to be restarted (p = 0.051), a higher proportion being ventilated on day 10 (p = 0.027) with higher Fio 2 (p = 0.001) and mean airway pressure (p = 0.002). Their chest radiographs showed more emphysematous changes as early as day 5 (p = 0.045), with a pronounced difference by day 10 (p = 0.009). Conclusions: Preterm ventilated babies with U urealyticum in their tracheal secretions have a different clinical and radiological course, with less acute lung disease but early onset of CLD, compared with those with negative cultures.